Traditional Versus Online Biology Courses: Connecting Course Design and Student Learning in an Online Setting - Rachel Biel (American Society for Microbiology, 2016)
Online courses are a large and growing part of the undergraduate education landscape, but many biology instructors are skeptical about the effectiveness of online instruction. We reviewed studies comparing the effectiveness of online and face-to-face (F2F) undergraduate biology courses. Five studies compared student performance in multiple course sections at community colleges, while eight were smaller scale and compared student performance in particular biology courses at a variety of types of institutions. Of the larger-scale studies, two found that students in F2F sections outperformed students in online sections, and three found no significant difference; it should be noted, however, that these studies reported little information about course design. Of the eight smaller scale studies, six found no significant difference in student performance between the F2F and online sections, while two found that the online sections outperformed the F2F sections. In alignment with general findings about online teaching and learning, these results suggest that well-designed online biology courses can be effective at promoting student learning. Three recommendations for effective online instruction in biology are given: the inclusion of an online orientation to acclimate students to the online classroom; student-instructor and student-student interactions facilitated through synchronous and asynchronous communication; and elements that prompt student reflection and self-assessment. We conclude that well-designed online biology courses can be as effective as their traditional counterparts, but that more research is needed to elucidate specific course elements and structures that can maximize online students’ learning of key biology skills and concepts.